PENGARUH PEMBERIAN SEDUHAN TEH DAUN SUKUN (Artocarpus altilis) TERHADAP TEKANAN DARAH DAN KADAR GLUKOSA DARAH PADA LANSIA DI DESA KENANGAN BARU - She Hartaty Vanya Liliasi Silalahi; Rostime Hermayerni Simanullang (Indonesian Trust Nursing Journal, 2026)
The increasing cases of hypertension and diabetes mellitus are health problems that are often experienced by the elderly and carry the risk of causing serious complications. One alternative complementary therapy widely used in the community is the use of breadfruit leaves (Artocarpus altilis), which are known to contain flavonoids, polyphenols, and saponins that play a role in lowering blood pressure and blood glucose levels. The purpose of this study was to determine the effect of steeping breadfruit leaf tea (Artocarpus altilis) on blood pressure and blood glucose levels in the elderly. This research method is a quantitative study with a quasi-experimental design with a one-group pretest-posttest approach. A sample of 25 people was obtained through total sampling. Data analysis used the Wilcoxon Signed Rank Test. The results showed that there was a decrease in blood pressure and blood glucose levels after the administration of breadfruit leaf tea. The results of the statistical test showed a p value <0.05, which means there was a significant effect of breadfruit leaf tea on reducing blood pressure and blood glucose levels in the elderly. Therefore, it was concluded that breadfruit leaf tea infusion had an effect on reducing blood pressure and blood glucose levels. It is recommended that future researchers add a Body Mass Index (BMI) variable.